Structural-Functional Classification cum Analysis of the Complete Sentences of Contemporary Nigerian Advertisement Messages (Global Journal of Human-Social Science, 2011)
Many of the contemporary Nigerian advertisements copy messages are simply phrases and sentence fragments while many others are syntactically and semantically complete sentences. The complete sentences of contemporary Nigerian advertisement messages are usually of different structural and functional classifications. This paper therefore attempts a structural-functional classification cum analysis of one hundred and fifty (150) complete-sentence advertisement messages identified among some selected three-hundred (300) advertisement messages of products, services, ideas or organisations i.e. 50% of the total. Seventy-six (76) of the complete-sentence advertisement messages i.e. 50.7% of the total are simple sentences of different functional classifications. Forty four (44) of the complete-sentence advertisement messages i.e. 29.3% are compound sentences of different functional classifications. The remaining thirty (30) complete-sentence advertisement messages i.e. 20% are complex sentences. None of the one hundred and fifty (150) complete-sentence advertisement messages is a compound-complex sentence.
Keywords: Complete Sentences; Advertisement Messages; Classification cum Analysis